Three dimensional evaluation of alveolar bone changes in response to different rapid palatal expansion activation rates - LaBlonde,Brian (2017)
ABSTRACT Introduction: The aim of this multi-center retrospective study was to quantify the changes in alveolar bone height and thickness after using two different rapid palatal expansion (RPE) activation protocols, and to determine whether a more rapid rate of expansion is likely to cause more adverse effects, such as alveolar tipping, dental tipping, fenestration and dehiscence of anchorage teeth. Methods: The sample consisted of pre- and post-expansion records from 40 subjects (age 8-15 years) who underwent RPE using a 4-banded Hyrax appliance as part of their orthodontic treatment to correct posterior buccal crossbites. Subjects were divided into two groups according to their RPE activation rates (0.5 mm/day and 0.8 mm/day; n = 20 each group). Three-dimensional images for all included subjects were evaluated using Dolphin Imaging Software 11.7 Premium. Maxillary base width, buccal and palatal cortical bone thickness, alveolar bone height, and root angulation and length were measured. Significance of the changes in the measurements was evaluated using Wilcoxon signed-rank test and comparisons between groups were done using ANOVA. Significance was defined at p ≤ 0.05. Results: RPE activation rates of 0.5 mm per day (Group 1) and 0.8 mm per day (Group 2) caused significant increase in arch width following treatment; however, Group 2 showed greater increases compared to Group 1 (p < 0.01). Buccal alveolar height and width decreased significantly in both groups. Both treatment protocols resulted in significant increases in buccal-lingual angulation of teeth; however, Group 2 showed greater increases compared to Group 1 (p < 0.01). Conclusion: Both activation rates are associated with significant increase in intra-arch widths. However, 0.8 mm/day resulted in greater increases. The 0.8 mm/day activation rate also resulted in more increased dental tipping and decreased buccal alveolar bone thickness over 0.5 mm/day.